Batch Adsorption of Tannins from Stevia Leaf Extract using Activated Carbon: An Investigation into Adsorption Isotherms and Adsorption Energy - Dewi, Luthfi Kurnia; Purwandaru, Kresna; Maulida, Nurul Istikomah; Sarosa, Aji Hendra (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Stevia leaf extract (Stevia rebaudiana Bertoni) could have been utilized as an alternative natural sweetener because it possessed a sweetness level 300 times that of sucrose sugar. However, stevia leaf extract still contained a bitter taste attributed to the presence of tannins. The method that can be used to reduce tannin content is batch adsorption using activated carbon. This study aimed to investigate the batch adsorption process for the tannin content of stevia leaf extract using activated carbon with variable adsorption times ranging from 5 to 180 minutes, which included the appropriate adsorption isotherm model and adsorption energy. Stevia leaves were extracted through maceration with 70% ethanol. The results of the stevia leaf extract were adsorbed in batches using activated carbon treated with 1M NaOH. The analysis was carried out by testing the tannin content (mg/g TAE) using a UV-Vis spectrophotometer at a wavelength of 735 nm and calculating the adsorption isotherm and adsorption energy. The results showed that the tannin content before adsorption was 0.910 mg/g TAE, and the lowest tannin content was 0.040 mg/g TAE at 100 minutes. The tannin content decreased between 590 minutes, remained constant, reached equilibrium at 95120 minutes, and increased again at 125180 minutes. The suitable adsorption isotherm model was the Freundlich isotherm with a value of R2 = 0.9998; KF = 25.293 [(mg/g)(L/mg)1/nf], and adsorption energy = -8.03 kJ/mol. The adsorption that occurred was classified as physical adsorption.